Program Santripreneur Melalui Pelatihan Ide Bisnis Repacking Snack Di Pesantren Tahfidz La Tahzan - sari, silvia; Margie, Lyandra Aisyah; Purwatiningsih (Abdimisi, 2025)
Community Service entitled the Santripreneur Program through Snack Repacking Business Idea Training at the La Tahzan Cinangka Depok Tahfidz Islamic Boarding School aims to foster the entrepreneurial spirit of students, identify effective ways to grow creative ideas into business opportunities, and explore approaches based on Islamic values ​​in developing entrepreneurship in Islamic boarding schools. This activity was carried out on March 20-21, 2025 at the La Tahzan Tahfidz Islamic Boarding School - Cinangka, Sawangan, Depok. The training activities began by providing training materials to 20 students, then a snack repacking technique training session by UNPAM lecturers from Accounting. The expected results are the growth of the entrepreneurial spirit of students, identification of effective ways to grow creative ideas into business opportunities, and exploration of Islamic value-based approaches in entrepreneurship.   Keywords: Santripreneur Program; Business Idea Training for Santri; Repacking Snacks